A thready affair: linking fungal diversity and community dynamics to terrestrial decomposition processes - van der Wal, Annemieke; Geydan, Thomas D.; Kuyper, Thomas W.; de Boer, Wietse (FEMS microbiology reviews, 2013)
Abstract Filamentous fungi are critical to the decomposition of terrestrial organic matter and, consequently, in the global carbon cycle. In particular, their contribution to degradation of recalcitrant lignocellulose complexes has been widely studied. In this review, we focus on the functioning of terrestrial fungal decomposers and examine the factors that affect their activities and community dynamics. In relation to this, impacts of global warming and increased N deposition are discussed. We also address the contribution of fungal decomposer studies to the development of general community ecological concepts such as diversity–functioning relationships, succession, priority effects and home–field advantage. Finally, we indicate several research directions that will lead to a more complete understanding of the ecological roles of terrestrial decomposer fungi such as their importance in turnover of rhizodeposits, the consequences of interactions with other organisms and niche differentiation. This review discusses the functioning of terrestrial decomposer fungi and examines the factors that affect their activities and community dynamics.